2012
DOI: 10.5402/2012/482802
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Alcohol Dependence and Depression before and after Treatment for Alcohol Dependence

Abstract: The presence of depression in alcohol-dependent persons is likely to influence treatment process and outcomes. Identification of depression is important though not every depressed alcohol-dependent person requires treatment with antidepressants. Understanding the association between depression and alcohol dependence is essential for proper management of alcohol dependence. Objectives. To determine the prevalence of depression among alcohol-dependent persons before and after alcohol detoxification and rehabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
66
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 46 publications
9
66
2
2
Order By: Relevance
“…The socio-demographic distribution is similar to the findings of an earlier study in East Africa. 1 The occurrence of clinically significant depression among participants who reported problems with alcohol use in our study was 31.1%. Prior studies have often reported an association with depression with greater risk with increasing use of alcoholic beverage.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The socio-demographic distribution is similar to the findings of an earlier study in East Africa. 1 The occurrence of clinically significant depression among participants who reported problems with alcohol use in our study was 31.1%. Prior studies have often reported an association with depression with greater risk with increasing use of alcoholic beverage.…”
Section: Discussionmentioning
confidence: 88%
“…Alcohol use has been postulated by some authors to be a predisposing/causal factor to depression while others are of the view that depression underlies majority of cases of alcohol use disorders. 1,6,7 Till date there is no clear consensus among researchers on the nature of the relationship. Co-occurrence of depression in those with problematic use of alcohol may lead to a pattern of self-medication of depressive symptoms with alcohol, increased rate of relapse after treatment, high utilization of health services and risk of suicide.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations